'A nation of town criers': civic publicity and historical pageantry in inter-war Britain. (24th February 2016) - HULME, TOM
ABSTRACT: Historical pageantry emerged in 1905 as the brainchild of the theatrical impresario Louis Napoleon Parker. Large casts of volunteers re-enacted successive scenes of local history, as crowds of thousands watched on, in large outdoor arenas. As the press put it, Britain had caught 'pageant fever'. Towards the end of the 1920s, there was another outburst of historical pageantry. Yet, in contrast to the Edwardian period, when pageants took place in small towns, this revival was particularly vibrant in large industrial towns and cities. This article traces the popularity of urban pageantry to an inter-war 'civic publicity' movement. In doing so, it reassesses questions of local cultural decline; the role of local government; and the relationship of civic responsibility to popular theatre.